Low‐Coordinated Pd Site within Amorphous Palladium Selenide for Active, Selective, and Stable H2O2 Electrosynthesis - Yu, Zhiyong; Lv, Shengyao; Yao, Qing; Fang, Nan; Xu, Yong; Shao, Qi; Pao, Chih‐Wen; Lee, Jyh‐Fu; Li, Guoliang; Yang, Li‐Ming; Huang, Xiaoqing (Advanced materials (Weinheim), 2023)
The development of high‐performance catalysts with high activity, selectivity, and stability are essential for the practical applications of H2O2 electrosynthesis technology, but it is still formidably challenging. It is reported that the low‐coordinated structure of Pd sites in amorphous PdSe2 nanoparticles (a‐PdSe2 NPs) can significantly boost the electrocatalytic synthesis of H2O2. Detailed investigations and theoretical calculations reveal that the disordered arrangement of Pd atoms in a‐PdSe2 NPs can promote the activity, while the Pd sites with low‐coordinated environment can optimize the adsorption toward oxygenated intermediate and suppress the cleavage of O–O bond, leading to a significant enhancement in both the H2O2 selectivity and productivity. Impressively, a‐PdSe2 NPs/C exhibits high H2O2 selectivity over 90% in different pH electrolytes. H2O2 productivities with ≈3245.7, 1725.5, and 2242.1 mmol gPd−1 h−1 in 0.1 m KOH, 0.1 m HClO4, and 0.1 m Na2SO4 can be achieved, respectively, in an H‐cell electrolyzer, being a pH‐universal catalyst for H2O2 electrochemical synthesis. Furthermore, the produced H2O2 can reach 1081.8 ppm in a three‐phase flow cell reactor after 2 h enrichment in 0.1 m Na2SO4, showing the great potential of a‐PdSe2 NPs/C for practical H2O2 electrosynthesis. Amorphous PdSe2 nanoparticles (a‐PdSe2 NPs) with low‐coordinated Pd sites have been successfully prepared and applied as highly efficient catalysts for H2O2 electrosynthesis. The low‐coordinated Pd sites with disordered arrangement in a‐PdSe2 NPs canoptimize the adsorption toward oxygenated intermediate and suppress the cleavage of O–O bond, leading to significant enhancement on the catalytic performance toward H2O2 electrosynthesis.